2007
DOI: 10.1213/01.ane.0000256863.92050.d3
|View full text |Cite|
|
Sign up to set email alerts
|

The Effects of Levosimendan in Cardiac Surgery Patients with Poor Left Ventricular Function

Abstract: In cardiac surgery patients with a low preoperative ejection fraction, stroke volume was better maintained with the combination of dobutamine with levosimendan than with the combination of dobutamine with milrinone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
87
1
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(104 citation statements)
references
References 38 publications
11
87
1
5
Order By: Relevance
“…Mortality was similar in the two groups [18]. De Hert et al have published a prospective randomised study of 30 patients with a LVEF 30% who received either levosimendan and dobutamine or milrinone and dobutamine [19]. In contrast to our work, De Hert showed that levosimendan resulted in a higher postoperative SVI compared to controls.…”
Section: Discussioncontrasting
confidence: 62%
“…Mortality was similar in the two groups [18]. De Hert et al have published a prospective randomised study of 30 patients with a LVEF 30% who received either levosimendan and dobutamine or milrinone and dobutamine [19]. In contrast to our work, De Hert showed that levosimendan resulted in a higher postoperative SVI compared to controls.…”
Section: Discussioncontrasting
confidence: 62%
“…They used loading dose of 12 ug/kg over 10 mins followed by 0.1 ug/kg/min for 12 hrs and showed that cardiac index, stroke volume, was significantly increased but systemic vascular resistance and PCWP was significantly low. De Hert, et al [20] have recently shown that Levosimendan in combination with dobutamine maintained stroke volume better than milrinone, in combination with dobutamine in cardiac surgery patients with a preoperative ejection fraction <30%. Tritapepe et al [21] showed that lower postoperative Troponin-I levels with levosimendan prophylaxis .…”
Section: Discussionmentioning
confidence: 99%
“…1 shows the flow of studies and the reasons for exclusion. Of the trials included, 16 [12][13][14]17,18,[31][32][33][34][35][36][37][38][39][40][41] Table 2 Summary of the validity assessments of randomised clinical trials of levosimendan in patients with acute severe heart failure.…”
Section: Study Characteristicsmentioning
confidence: 99%